The diffusion of Lean in the Norwegian municipality sector: An exploratory survey - Dag Øivind Madsen; Stig Risvik; Tonny Stenheim (Cogent Business & Management, 2017)
The use and application of Lean in the public sector has attracted considerable interest in recent years. In Norway, the concept of Lean has lately been hugely popular, not only among private sector firms, such as manufacturers, but increasingly also in the public sector where Lean has been proposed as a management tool that can improve the productivity and performance of, for example, municipalities. There have been several initiatives suggesting and recommending Lean adoption and implementation in the municipality sector. However, little is known about how and to what extent Lean is currently used by Norwegian municipalities. Therefore, this paper examines the diffusion of Lean among Norway's 426 municipalities, by means of an exploratory survey that yielded a response rate of about 25 percent. The survey results generally show that the awareness and adoption of Lean has increased quite sharply in recent years. Most municipalities have recently adopted and started using the Lean concept, and the concept appears to be in a relatively early stage of its lifecycle in the Norwegian municipality sector. When it comes to implementation of the Lean concept, the municipalities vary in terms of how they apply and utilize Lean. For example, the survey data indicate that municipalities use a broad spectrum of Lean-related tools and techniques. Finally, while the perceived effects of Lean are generally positive, there are also a range of issues and challenges associated with the implementation of Lean in municipalities.
Keywords: 650